Некоторые технические решения реализации интерфейса человек-устройство - Губанов, Александр Вячеславович; Жемчужкина, Татьяна Владимировна; Носова, Татьяна Витальевна; Носова, Яна Витальевна (НТУ "ХПИ", 2015)
Проблема управления внешними устройствами с помощью различных интерфейсов является актуальной. В статье проанализированы существующие технические решения реализации интерфейсов человек-устройство, определены основные недостатки (проводная связь между сегментами и управляемым устройством, наличие выносного опорного электрода), предложены решения для их устранения. Разработаны структурная и функциональная схемы устройства, основанного на регистрации электромиографического сигнала с учетом положения объекта в пространстве.

Recognition of gestures is an actual and important problem. This technology can be applied in various fields of human activity: management of computers and household appliances, creation of a natural human-machine interfaces for the deaf people, manipulation of three-dimensional models of objects, virtual reality applications, management of multicopters and exoskeletons. The purpose of this work is to analyze existing technical solutions of the human interface device implementations and identify disadvantages of these devices, as well as offer some technical solutions to eliminate these disadvantages. There are many fundamentally different systems that implement the motion detection of human limbs: systems using surface electromyography, systems using video camera, systems based on the emission and reception of infrared light, systems using different resistive sensors sewn into clothing.
Some technological solutions of realization of human interface device
Keywords: браслет; мышца; электромиография поверхностная; surface electromyography; bracelet; muscle